Rota do ouro: um estudo sobre o resgate da memória da mineração em Lavras do Sul através de seu conjunto arquitetônico urbano - Carvalho, Fernanda Ricalde Teixeira (2013)
This dissertacion presents a proposal for routing in the town of Lavras do Sul, with gold mining as the theme, rescuing the collective memory on the gold rush, through the buildings that were mills, power plants and homes mining engineers, who took up residence in the town and made it the first town in Rio Grande do Sul to have originated in gold mining. The structure of this dissertation constitutes the first chapter where we report the historical context of gold mining, from its inception to the present day. The second chapter is about the importance of preservation, redemption and research on the memory of the constructions of gold. As the final step, is to propose a roadmap as a practical result of the research. For the coverage area, it was decided that the route will be in the urban area, the front sides of the reference houses, and with some stops in public places related to the theme of gold, like old mills, ruins and also private homes which may be intended for touristic visits eleven points inventoried.